Conhecer, viver e formar: narrativas sobre a prática do professor na educação de jovens e adultos - MOREIRA, Maria das Graças (2015)
The study of qualitative approach, aims to analyze how the professor knows, lives and meets the demands of the students of the Technical Course in Computer Maintenance and Support, Middle Level, in the modality of Youth and Adult Education (PROEJA). For the development of our study, in addition to legal bases we seek support at the thought of Elias (1994), Mool (2010), Meihy (2011), Soares (2013) and Schwartz (1992). By understanding that the relationship between theory and practice requires reflection and shared work as fundamental to the effectiveness of this type of education, we understand the school as a space for multiple possibilities of production of knowledge, experiences and training. The empirical field will be the Technical Course in Computer Maintenance and Support (PROEJA at the Federal Institute of Education, Science and Technology of Rio de Janeiro (IFRJ). The universe of the subjects was made up of seven teachers through interviews focused on oral history . We have as expectations the contribution of the study for the improvement of the education in PROEJA, when we seek in the teaching practice, the knowledge, the experience and meeting the demands of the students.